Rights and responsibilities of alumni in the bylaws and Statutes of the Polish Pontifical College in Rome in 1960 - STĘPIEŃ, MAREK (Prawo Kanoniczne, 2012)
At the end of 1960, the Holy See approved new Bylaws and Statutes of the Pontifical Polish College in Rome. The Polish Pontifical College was identified as an institution having ecclesiasticallegal personality, which is responsible for educating and preparing students from Polish dioceses to become ordained as priests. Primarily, these documents relate to students who were preparing to receive the sacrament of Holy Orders. A great emphasis was placed on the study of philosophy and theology. Since 1963, only priests resided at the Polish Pontifical College that were sent by their diocesan bishops for specialized studies in Rome. The Bylaws and Statutes require that the students show a vocation to the service of God, be exemplary role models, have good character, good health and needed talents. Special attention was given to the importance of spiritual development of the students. The bylaws emphasize the importance of the seminarian’s pursuit of his vocation or a priest’s holiness, by maintaining an appropriate spiritual life. Students are also required to constantly and consistently gain intellectual knowledge, in accordance to the bylaws laid down by the Holy See and their bishops. The last part of the Bylaws stresses the importance of discipline, stating the general standards, the responsibilities of the alumni in regards to College personnel and students, as well as providing the daily agenda.